Oxidation of Substituted Phosphanylboranes with Chalcogens. Issue 18 (8th March 2017) - Marquardt, Christian; Hegen, Oliver; Kahoun, Tobias; Scheer, Manfred
Abstract: The elemental chalcogens sulfur, selenium, tellurium and bis(trimethylsilyl)peroxide as an oxygen source are applied for the oxidation of the phosphanylboranes Ph2 P‐BH2 ⋅NMe3 (1 ) and t BuHP‐BH2 ⋅NMe3 (2 ). The corresponding monooxidation products Ph2 P(X)‐BH2 ⋅NMe3 (X=O–Te, 3 a –d ) and t BuHP(X)‐BH2 ⋅NMe3 (X=O–Te, 4 a –d ) were obtained in good yields and comprehensively characterized by single crystal X‐ray structure analysis, NMR, IR spectroscopy and mass spectrometry. The first oxidation step proceeds very selectively for all chalcogenides. For the t Bu derivative, a further oxidation can be realised with O2, S8 and Se yielding t Bu(HX)P(X)‐BH2 ⋅NMe3 (X=O, S, Se, 5 a –c ). The telluride compounds presented herein are the first examples of neutral Te‐substituted phosphanylboranes. Abstract : Oxidation time ! Stoichiometric reaction of the phosphanylboranes Ph2 P‐BH2 ⋅NMe3 and t BuHP‐BH2 ⋅NMe3 with elemental chalcogens or peroxides leads to the mono‐oxidized species. Thus, first derivatives of neutral B‐P‐Te‐containing compounds have been isolated. In the case of the secondary phosphanylborane, further oxidation is also possible.